PENGARUH STRUKTUR DAN AKTIVITAS GOOD CORPORATE GOVERNANCE TERHADAP LUAS PENGUNGKAPAN INFORMASI STRATEGIS SECARA SUKARELA PADA WEBSITE PERUSAHAAN YANG TERDAFTAR DALAM BURSA EFEK INDONESIA - Gedie E Siagian; Imam Ghozali (Diponegoro Journal of Accounting, 2012)
Many factors affect the extent of strategic information may be disclosed by the company, especially through the website. This study is a replication of the research Sanchez et al (2008). However, only some of the variables used in this study, adapted to the situation of companies in Indonesia. Corporate governance is essentially comes to controlling the behavior of top executives to protect the interests of stakeholders. The problem arises because of the separation between ownership and management company. The separation is explained by the theory of the Agency in terms of the so-called agency problem. This study aimed to test whether there is a positive relationship between the size of the board of commissioners, commissioners activity, the proportion of independent board of directors, audit committee activity, firm size and industry type to extensive voluntary disclosure of strategic information on the company website. The research was conducted by the method of observation and documentation of the companies listed on the Stock Exchange in 2010 and has a website as a population consisting of 426 companies. After making observations, eventually acquired 126 companies. To analyze the effect of the independent variable on the dependent variable, linear regression analysis was used to test the assumption that preceded classical. The results showed that the activities of the audit committee and firm size wide significant positive effect on the company’s strategic disclosure. While the activities of the board, proportion of independent commissioners, and industry types have positive but not statistically significant. For the size of the board of commissioners, proved to negatively affect the company’s broad strategic disclosure.